Health Education during the COVID-19 Pandemic: A Bibliometric Analysis - Yunindyawati (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
The COVID-19 pandemic has drastically increased global mortality, underscoring the urgent need for effective health education. This study examines health education literature during the pandemic, focusing on articles published from 2018 to 2022, sourced from the Dimensions Database. Using bibliometrics and VOSviewer for visualization, 2,500 articles were analyzed based on publication trends, contributions by countries, institutions, and authors, journal distribution, highly cited articles, and bibliographic coupling. The findings reveal that the United States, the United Kingdom, China, Canada, and Australia are the primary contributors to health education publications. Notably, the University of Michigan-Ann Arbor, the University of California, Los Angeles, and Johns Hopkins University emerged as leading institutions regarding document count and citations. The most cited article, "Consumer Attitudes Towards Environmental Concerns of Meat Consumption: A Systematic Review" by Sanchez-Sabate & Sabaté, published in the International Journal of Environmental Research and Public Health, reached 148 citations. This analysis highlights the significant global contributions to health education research during the pandemic, identifying key institutions and influential works. These insights are vital for researchers and policymakers aiming to enhance health education strategies in response to global health crises.